Oil rents dependence, oil prices and exchange rates : evidence from daily data - Budkov, Roman; Zouhar, Jan, 1982-; Formánek, Tomáš; Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky (2017)
This paper studies the relationship between the oil prices and exchange rates of oil exporting countries, in terms of their dependence on oil rents. The study is based on data at the daily frequency over the period 2005-2015. In the first chapter, the data set and basic characteristics of the countries are described. The second chapter represents the econometric framework for the practical section. Applying a vector error correction model mainly produced controversial results. Analysis based on a GARCH approach found a positive relationship between the value of the currencies and the oil prices, although the link with the oil rents dependence is not sufficiently evident. The paper also supports stylized facts, such as a negative relationship between the U.S. dollar value and the oil prices.
Vedoucí práce: Jan Zouhar
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky, 2017
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2017
Způsob přístupu: Internet
Keywords: matematické metody v ekonomii [obor bakal. práce]; bakalářské práce; bachelor's theses